Fiscal reform in Spanish municipalities: Gender differences in budgetary adjustment - Israel García; Bernd Hayo (Philipps-University Marburg, School of Business and Economics, 2023)
Do gender differences matter for politicians' budgetary behaviour when confronted with an exogenous change in the institutional framework? After the 2013 Spanish municipal reform, municipalities with more than 20,000 inhabitants were no longer responsible for managing the provision of social services. Using a difference-in-differences estimator in a sample of municipalities from the Madrid region for 2010-2019, we compare gender differences in social services spending before and after the reform between municipalities below 20,000 inhabitants (control group) and above 20,000 inhabitants (treatment group). Although social spending was, on average, significantly reduced in the treatment group post-reform, we observe significant differences between municipalities conditional on the gender composition of local governments, i.e. council and mayor. Whereas male-dominated governments cut social expenditure by about 20% of the total budget, gender-balanced and female-dominated governments did not. Moreover, gender-balanced governments combined with female mayors increased social services spending by 40% more than gender-balanced governments combined with male mayors. This finding supports the claim that social spending is, on average, of particular importance to female politicians, as they are willing to bend the law to uphold their interests.
Keywords: C23; E61; D72; H75; I38; J16; 330; Gender; Difference-in-differences; Exogenous reform; Political budget cycles; Spanish municipalities; Madrid region